Wind, solar, and beyond: unlocking the value of EDP Renewables in the green economy - Ye, Sónia (2024)
This report analyses EDP Renováveis, S.A. (EDPR), examining both the challenges and opportunities within the industry, which is currently facing uncertainties, particularly with the re-election of President Trump in the United States, which may impact policy support for renewables. Financial forecasts and multiple valuation methods were employed, including Discounted Cash Flow (DCF) analysis, sensitivity analysis, scenario analysis, and Monte Carlo simulations. The analysis concludes with a final target price of €13.29, representing a potential upside of 30%, leading to a BUY recommendation. This reflects the belief that despite current challenges, EDPR remains well-positioned to deliver strong long-term value for investors.